Moral Surveillance in Shariah Law: Between Misconception and Significance - Syed Salim Syed Shamsuddin (IKIM Press, 2024)
Since the start of creation, man has never ceased to contemplate the moral question of good and evil. Morality basically refers to principles concerning right and wrong or good and bad behavior. It deals with human's character and conduct that to be governed by certain rules. In Islamic point of view, Islamic morality teaches the Muslim how to win the never-ending battle of good against evil as prescribed by Allah (s.w.t.). Morality is both an individual and social phenomenon. Thus, the relevance of morals to our daily life is so great that a lot of our present social, economic and political problems are the result of our ethical problem.